Idaho - Kent, Zachary (Chicago : Childrens Press, 1990)
Introduces the geography, history, government, economy, industry, culture, historic sites, and famous people of the Gem State.
Includes index.
Elem. School Library Collection
6.7
5-8
Keywords: Idaho -- Juvenile literature; Idaho; Idaho